Yellowstone's survival a call to action for a new conservation story - Clark, Susan G. 1942- (Anthem Press, 2021)
This book focuses on Yellowstone: the park, the larger ecosystem, and even more so, the 'idea' of Yellowstone. In presenting a case for a new conservation paradigm for the Greater Yellowstone Ecosystem (GYE), including Yellowstone National Park, the book, at its heart, is about people and nature relationships. This new paradigm will be truly committed to a healthy, sustainable environment, rich in other life forms, and one that affords dignity for all: humans and nonhumans. The new story or paradigm must be about living such a commitment and future for GYE in real time. The book presents a well-developed theory for interdisciplinary problem solving that is grounded in practice
Title from publisher's bibliographic system (viewed on 21 May 2021)
Keywords: Nature conservation / Yellowstone National Park Region; Ecosystem management / Yellowstone National Park Region; Human beings / Effect of environment on / Yellowstone National Park Region; Nature / Effect of human beings on / Yellowstone National Park Region; Yellowstone National Park